Development of a Measure of Classroom Assessment Practices for Certification of Accomplished Teachers - Ezzelle, Carol (Frontiers in Education, 2019)
Teachers pursuing National Board Certification complete a rigorous assessment comprised of four components measuring standards of accomplished pedagogical knowledge and practice. One of those components of the assessment, Component 4: Effective and Reflective Practitioner, is a new performance-based portfolio component that centers on the use of assessment data and other sources of information to advance student and teacher growth. Specifically, the component requires teachers to: • gather and utilize data from different sources to build their knowledge and understanding of students; • base instructional decision-making and assessment practices on their knowledge of students, collaboration with stakeholders, and adherence to assessment principles; and • use their knowledge of students to reflect on their practice, advance their professional learning, and promote student growth throughout learning communities. The development and outcomes of the pilot test of Component 4: Effective and Reflective Practitioner related to establishing validity evidence for the component's scores as a measure of accomplished teaching are described. The methods reported cover the use of experts in the development of instructions, a pilot study, and formative scoring to build evidence of the validity based on test content and ensure the successful launch of the new component.